1994
DOI: 10.1105/tpc.6.11.1583
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Arabidopsis Mutant That Is Nonresponsive to Inducers of Systemic Acquired Resistance.

Abstract: Systemic acquired resistance (SAR) is a general defense response in plants that is characterized by the expression of pathogenesis-related (PR) genes. SAR can be induced after a hypersensitive response to an avirulent pathogen or by treatment with either salicylic acid (SA) or 2,6-dichloroisonicotinic acid (INA). To dissect the signal transduction pathway of SAR, we isolated an Arabidopsis mutant that lacks the expression of an SA-, INA-, and pathogen-responsive chimeric reporter gene composed of the 5[prime] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
646
0
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,110 publications
(668 citation statements)
references
References 21 publications
15
646
0
7
Order By: Relevance
“…Plants were grown during 4 weeks in a 12 h light/12 h dark cycle with 60-70% of relative humidity, with a day temperature of 20-22 • C and a night temperature of 16-18 • C. A. thaliana ecotype Columbia-0 (Col-0) wild-type plants were obtained from the Nottingham Arabidopsis Stock Centre (Nottingham, UK), transgenic seeds over-expressing the salicylate hydroxylase NahG gene were obtained from J. Ryals [23]. The following A. thaliana mutants (all in the Col-0 background) were used and previously described: jar1-1, coi1-16, etr1-1, ein2-1 [24], ics1 [25], npr1 [26], and dde2.1 [27].…”
Section: Plant Maintenancementioning
confidence: 99%
“…Plants were grown during 4 weeks in a 12 h light/12 h dark cycle with 60-70% of relative humidity, with a day temperature of 20-22 • C and a night temperature of 16-18 • C. A. thaliana ecotype Columbia-0 (Col-0) wild-type plants were obtained from the Nottingham Arabidopsis Stock Centre (Nottingham, UK), transgenic seeds over-expressing the salicylate hydroxylase NahG gene were obtained from J. Ryals [23]. The following A. thaliana mutants (all in the Col-0 background) were used and previously described: jar1-1, coi1-16, etr1-1, ein2-1 [24], ics1 [25], npr1 [26], and dde2.1 [27].…”
Section: Plant Maintenancementioning
confidence: 99%
“…NH1 is the ortholog of Arabidopsis NPR1, is a key regulator of the SA-mediated systemic acquired resistance (SAR) [4,35]. NPR1 encodes a novel protein with a bipartite nuclear localization sequence.…”
Section: Regulation Of Production Of Herbivore-induced Air-borne Mesamentioning
confidence: 99%
“…More than a decade ago, additional components downstream of signaling molecules SA, JA and ethylene were characterized in several mutant plants, such as the jasmonate response mutant jar [26], the ethylene response mutant etr [27] and the SAR regulatory mutant npr1 [28]. In a genetic screening for plants failed to express PR genes after SAR induction, npr1 mutant was isolated in Arabidopsis [28] and NPR1 gene was cloned [29].…”
Section: Introductionmentioning
confidence: 99%
“…In a genetic screening for plants failed to express PR genes after SAR induction, npr1 mutant was isolated in Arabidopsis [28] and NPR1 gene was cloned [29]. Further results revealed that NPR1 was a key regulator of SA-mediated SAR in Arabidopsis [30][31][32].…”
Section: Introductionmentioning
confidence: 99%